PENINGKATAN PENGETAHUAN DAN KETERAMPILAN PELAKU USAHA DALAM MENGIMPLEMENTASIKAN PROSES PRODUK HALAL - Leksono, Amin Setyo; Herawati, Herawati; Azrianingsih, Rodiyati; Qurotaayuina, Riska Putri (JURNAL PENGABDIAN PAPUA, 2024)
The community service activity in the Kasembon area was focused on the community of Sukosari Village, Kasembon District, which has significant potential in product development through local SMEs. However, the lack of knowledge and skills in halal production and certification has become an obstacle. Therefore, this activity aims to improve the knowledge and skills of business actors in halal product processes and slaughtering techniques. The methods used include site surveys, involving the Kasembon Business Destination Association (PADUKA), followed by education and mentoring. The activity was attended by 20 participants, consisting of business actors and prospective halal slaughterers. Based on the results, it can be concluded that education/presentation increased the participants' knowledge, motivation, and interest in implementing halal product processes and certification in Kasembon SMEs. The participants' initial knowledge regarding halal product process criteria was quite good, but many were still unaware of the differences between self-declaration and regular certification, the Halal Product Assurance System Manual Document, halal slaughtering processes, and marketing strategies. With counseling and training, participants' knowledge and awareness increased significantly. As a result, participants' understanding increased from 15-60% to 30-50%, with a satisfaction rate of 50% being very satisfied, 45% satisfied, and 75% committed to following up, developing, and supporting halal product certification in Kasembon. Keywords: halal product; halal certification; UMKM.